Neonatal Seizures with Diffuse Cerebral White Matter Lesions on Magnetic Resonance Imaging Associated with Rotavirus Infection: A Report of Three Cases - Min Seon Choi; Sang Kee Park; Jae Hee Lee (Korean Society of Neonatology, 2018)
Rotavirus is the major cause of gastroenteritis in children under the age of 5. Rotavirus infection may lead to several neurological complications as meningitis, encephalitis, convulsion, encephalopathy, hemorrhagic shock, central pontine myelinolysis, Guillain-Barre syndrome, and Reye's syndrome. Further, some reports have described diffuse cerebral white matter lesions on diffusion-weighted magnetic resonance imaging (MRI) in neonates with rotavirus induced seizures. Here, we report on three neonates with rotavirus induced seizures with cerebral white matter abnormalities on MRI.